The study of pedagogical communication in teaching some subjects through the Flanders network of class verbal interaction - حسين مشطر (International Journal of Social Communication, 2021)
The study aimed to identify the prevailing pedagogical communication pattern in the classroom in intermediate education - second year - through a comparison between mathematics didactic and didactic of Arabic language using the Flanders network to analyze classroom verbal interaction. The verbal behavior of the teacher and the students. The study concluded with the following results: - The prevailing classroom interaction pattern in mathematics was indirect, and according to Flanders, this pattern prevails when the educational objectives are ambiguous, and from this, we conclude that the nature of the communicative pedagogical discourse in mathematics is democratic. - The pattern of classroom interaction prevailing in the Arabic language was direct, and according to Flanders, this pattern prevails when the learners' perceptions of the educational goals are clear, and from it we conclude that the nature of the pedagogical communicative discourse in the Arabic language subject is